Functional Annotation of Some Hypothetical Genes in the Schistosoma Parasite Based on Reciprocal Best Structural-hit Relationship - Arezou Askari Rad; Jamal Fayazi; Mohammad Taghi Beigi Nassiri; Alireza Hasani Baferani (Research in Molecular Medicine)
Background: The Schistosoma parasite is responsible for several overlooked tropical diseases, which cause significant economic losses in livestock. This parasite is increasingly found in the central areas of the northern provinces of Iran. To generate an effective treatment, it is crucial to understand thoroughly how the parasite’s genes work. Currently, the roles of numerous genes in these parasites are unknown, so their identification and targeting of them are challenging. Conventional techniques for assigning functions to proteins depend on the similarity of their sequences. Yet, this method does not always recognize similarities between distantly related proteins. Research has shown that taking the protein’s structure in the process of predicting its function can be helpful in pinpointing proteins whose functions are not known yet. Methods: In our study, we utilized two advanced technologies, AlphaFold and Foldseek, to deduce the functions of theoretical proteins in the Schistosoma parasite. We accomplished this by contrasting the structure of Schistosoma proteins with those of Caenorhabditis elegans, a closely related model organism, using Foldseek to identify reciprocal best matches. Our research involved an in-depth examination of two specific predictions, evaluating evidence for functional resemblances, such as patterns of protein interactions and similarities in functional domains. Results: Our results indicate that one of the analyzed genes is likely involved in embryogenesis, while the other might be connected to the egg-laying process of the Schistosoma parasite. Conclusion: Function of some hypothetical proteins can be inferred bases on their structural similarities to annotated proteins, especially proteins with a low sequence similarity to annotated proteins.